2016
DOI: 10.1136/gutjnl-2015-310783
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin β receptor signalling executesHelicobacter pylori-driven gastric inflammation in a T4SS-dependent manner

Abstract: LTβR-triggered activation of alternative NF-κB signalling in gastric epithelial cells executes -induced chronic gastritis, representing a novel target to restrict gastric inflammation and pathology elicited by, while exclusively targeting canonical NF-κB may aggravate pathology by enhancing the alternative pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…2 The inflammatory reaction triggered by the bacterial infection is a key contributing factor to the development of chronic gastritis. 2 GECs provide the first point of contact between H pylori and the host, and play important roles in inflammatory reactions, thus, a better understanding of the cellular and molecular mechanisms of H pylori-associated chronic gastritis is urgently required. The cagA protein is a 120-140 kDa protein which can be injected into gastric epithelial cells (GECs) via the type IV secretion system (T4SS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The inflammatory reaction triggered by the bacterial infection is a key contributing factor to the development of chronic gastritis. 2 GECs provide the first point of contact between H pylori and the host, and play important roles in inflammatory reactions, thus, a better understanding of the cellular and molecular mechanisms of H pylori-associated chronic gastritis is urgently required. The cagA protein is a 120-140 kDa protein which can be injected into gastric epithelial cells (GECs) via the type IV secretion system (T4SS).…”
Section: Introductionmentioning
confidence: 99%
“…1 Chronic gastritis induced by H pylori can progress to atrophic gastritis, intestinal metaplasia, dysplasia, and ultimately gastric cancer (GC). 2 The inflammatory reaction triggered by the bacterial infection is a key contributing factor to the development of chronic gastritis. 3 The high levels of the inflammatory reaction to H pylori have been directly linked to the presence of microbial virulence factors, mainly the cagA (cytotoxin-associated gene A) protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New information was also provided on the mechanisms by which H. pylori virulence factors, including the cag type IV secretion system (T4SS) and vacuolating cytotoxin A (VacA), influence inflammation. Mejías-Luque et al 5 found that the cagT4SS is important in controlling expression of lymphotoxins (LTs). Activation of LT beta receptor (LTβR) signaling led to alternative NF-κB signaling.…”
Section: Epithelial Cell -Helicobacter Pylori Interactionsmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infects~4.4 billion individuals worldwide and is closely associated with chronic gastritis [1][2][3] . Chronic gastritis induced by H. pylori can progress to atrophic gastritis, intestinal metaplasia, dysplasia, and ultimately gastric cancer (GC) 3 .…”
Section: Introductionmentioning
confidence: 99%